Fostering productivity patterns, determinants, and policy implications - Gelauff, G. M. M. (Boston : Elsevier, 2004)
The main purpose of this book is to enhance the understanding of differences in productivity performance between countries and sectors and to improve our insight in the drivers of productivity levels and its growth. Due to demographics the speed-up of productivity growth will be of increasing importance to secure GDP growth in the future, since the other source of GDP growth (employment growth) will be limited in most Western Countries. A better insight in the patterns and drivers of productivity performance is therefore not simply a matter of academic interest, however valuable that in itself can be. Improving our knowledge of the drivers of productivity will enable us to determine which are the 'switches' policy makers have to use. The book takes the Netherlands as a case, but is hardly a book on productivity in the Low Countries alone. The different contributors focus on the drivers of productivity that prevail in every modern economy, using the Netherlands' experience as an example, which makes this book relevant for the analysis of productivity in other countries. Moreover, the book contains international comparisons between EU and OECD countries, in particular with regard to productivity performance. The book focuses on productivity in the business sector, leaving public sector productivity aside.
Introduction / Theo Roelandt -- Human capital and productivity : a labour market perspective / Anne Reitsma -- Wage moderation and labour productivity / Frederik Huizinga -- Integrating evidence on the determinants of productivity / Henri L.E. de Groot -- Four sources of innovation and stimulation of growth in the Dutch economy / William J. Baumol -- Market structure, innovation and productivity : a marriage with chemistry / Henry van der Wiel -- Firm dynamics and labour productivity / Wim Verhoeven -- The contribution of business services to aggregate productivity growth / Henk L.M. Kox -- Increasing productivity through innovation and entrepreneurship in business services / Menno van Dijk -- The OECD growth study : implications for the Netherlands / Dirk Pilat -- What do the numbers mean? / Bart van Ark -- A policy agenda for higher productivity growth / Theo Roelandt -- Helping thy neighbour : productivity, welfare and international trade / Ben Geurts -- R&D and innovation : drivers of productivity growth / Luuk Klomp -- An international comparison of productivity performance : the case of the Netherlands / Stephan Raes -- ICT and Productivity / George van Leeuwen.
Includes bibliographical references.
Description based on print version record.
Keywords: Industrial productivity; Industrial productivity -- Case studies; Business & Economics -- Industries -- General; Science -- General; Labour economics